Unique model of polarization engineered AlGaN/GaN based HEMTs for high power applications. (February 2015) - Jebalin, Binola K.; Shobha Rekh, A.; Prajoon, P.; Godwinraj, D.; Mohan Kumar, N.; Nirmal, D.
Highlights: A polarization based unique S/D Schottky contact HEMT model is designed and the results are calibrated with experimental data. The effect of mole fraction in aluminium of HEMT is studied and found the optimize value as 0.20 for Al it leads improvement in 2DEG. A new breakdown voltage model is developed and the simulation and mathematical results shows an improvement in breakdown voltage. High frequency is also obtained for the model and it is compared with the simulated results. Abstract: In this paper, a novel source/drain Schottky contact technology AlGaN/GaN HEMT device is designed and modelled. Based on this concept, effect of mole fraction in three different HEMT devices is studied using the unique mathematical model. An optimized Al0.2 Ga0.8 N/GaN HEMT shows an excellent improvement in sheet carrier density and breakdown voltage. Break down voltage (BV) is one of the major concerns in the present day High Electron Mobility Transistor device (HEMT). The proposed device with Lgd of 5 μm shows a breakdown voltage of 320 V, which is in good agreement with experimental data. In addition to this, drain current, transconductance and frequency is also modelled and simulated using TCAD. Hence Schottky based AlGaN/GaN HEMT is one of the promising candidates for high power applications.